REFORMULASI PIE SUSU MENGGUNAKAN BAHAN LOKAL MENUJU PRODUK UNGGULAN BOJONEGORO - Siswara, Hamzah Nata; Wulandari, Kartika; Huda, Khoirul; Mubarok, Amin; Saputro, Tri Hadi; Atho'illah, Muhammad Ahsan (Abdi Panca Marga, 2023)
Pie susu is a contemporary snack consisting of pie and filling. Pie susu production is still not massively carried out at Ngambon Vocational School. Production is only carried out when orders are received and there has been no effort to expand information to a wider range of potential consumers. The pie susu produced at Ngambon Vocational School still uses conventional ingredients and needs a touch of innovation. The method used is to add banana flour, local goat's milk, kemit durian (local to Bojonegoro), and Ngringinrejo starfruit as raw materials for making pie susu. Efforts made are 1. Socialization of Rebranding pie susu innovation 2. Strengthening production by carrying out processing according to GMP and SSOP, to meet food processing standards that comply with hygiene and sanitation 3. Determining raw material recipes and SSOP for pie susu production 4. Applying for permits PIRT distribution and halal certification. The product succeeded in using local raw materials, received PIRT distribution permits and halal certification, the process of registering a trademark, and the pie susu product was ready to be commercialized. The resulting pie susu has the potential to become Bojonegoro's superior product because the ingredients used are local ingredients from Bojonegoro Regency and produce an attractive contemporary pie susu. Keywords: pie susu, food innovation, rebranding